IMPROVING THE QUALITY OF MANAGEMENT IN COMMERCIAL BANKS ON THE BASIS OF INTERNATIONAL PRINCIPLES OF CORPORATE GOVERNANCE (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
This article discusses the issues of developing a corporate governance system in commercial banks, its organization based on international principles, and practical recommendations for improving the quality of governance. The need to introduce such basic principles as openness, accountability, fairness, and responsibility in the banking system is substantiated.